Evaluation of Insecticides for the Management of Litchi Fruit and Shoot Borer - Upadhyay, Sudeep Kumar; Aryal, Sunil; Bhusal, Bikash; Chaudhary, Bedanand (Journal of Nepal Agricultural Research Council, 2020)
Litchi is an important subtropical evergreen fruit crop grown in Nepal, which have high nutritive value and refreshing taste. The Litchi growers are experiencing severe loss every year with the damage caused by several insect pests. Among them fruit and shoot borer Conopomorpha sinensis Bradley (Lepidoptera: Gracillariidae) is the one of the important insect pests. Experiments were conducted at RARS Tarahara on existing litchi orchard in RCBD design with four replication and five insecticides (Azadiractin, Chlorantraniliprole, Flubendiamide, Lambda cyhalothrin, and Dimethoate) with recommended doses in litchi orchard against C. sinensis during 2015 and 2016 to find out the efficient one. Among the tested insecticide chlorantraniliprole (18.5% w/w SC) and flubendiamide (39.35% m/m SC) each were found to be most efficient against C. sinensis and could be applied at the rate of 1 ml per 3 liters of water when fruit size was about pea and applied 3 times with 10 days interval. This result suggested that these two insecticides could be used for the management for C. sinensis. Farmers may reduce the losses and increase their income with the application of these insecticides